Pengaruh Konseling Terhadap Motivasi Ibu dalam Pemberian ASI Eksklusif - Suhaibaton, Suhaibaton; Idawati, Idawati; Yustiananda, Yustiananda; Dewi Safitri; Mutiawati, Mutiawati (Yayasan Literasi Sains Indonesia, 2023)
Breast milk is the best food that can help the baby's growth and development process. The World Health Organization (WHO) recommends the Global Strategy for Infant and Young Child Feeding which are four essential things in infant and child feeding, one of which is breastfeeding only to infants up to 6 months of age, or what is called exclusive breastfeeding. Breast milk is seen as the most ideal nutritional intake for babies, because it is safe and contains antibodies that can prevent the onset of disease in infants and children. However, until now there are 2 out of 3 babies in the world who do not get exclusive breastfeeding for six months and have been for 2 decades (WHO, 2022). This study aims to determine the relationship between maternal knowledge about exclusive breastfeeding and the motivation for exclusive breastfeeding. This type of research is quantitative with a cross sectional approach. The conclusion obtained from this study is that there is a very significant positive relationship between counseling and maternal knowledge with the motivation for exclusive breastfeeding.